Pengaruh Kompetensi Kepribadian Guru Pendidikan Pancasila terhadap Karakter Tanggung Jawab Siswa SMP Negeri 1 Percut Sei Tuan - Situmorang, Winda Arisandi; Siregar, Hapni Laila (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This study aims to determine that the personality competence of Pancasila Education teachers can affect the character of responsibility of SMPN 1 Percut Sei Tuan students. The theory used is convergence theory. This research uses quantitative correlation method. The period of research implementation is from June 11 to July 12, 2024. Data gathering methods were conducted through observation, interviews, and documentation. The tools utilized for data acquisition in this research included Likert Scale surveys and open-ended questionnaires based on random sampling. The study participants were selected using a random sampling approach from a defined population of 309 students from a total of class VIII and a total sample of 40 students, with 4 representatives from each class. The types of data in this study are primary and secondary data. The data analysis techniques used are correlation test, determination test, hypothesis testing using a Likert scale. Data analysis in this study uses statistical quantitative methods with product moment calculations. This is evidenced by the calculation of the correlation coefficient between variable x and variable y, it is known that the rcount value is 0.563. If this value is compared with the rtable value at a significant 5% with n = 40, then the rcount is equal to the provisions, if the rcount value is greater than the rtable (0.563> 0.312) then, it can be concluded that there is a significant influence on the influence of the personality competence of the Pancasila Education teacher on the character of student responsibility in class VIII of SMP Negeri 1 Percut Sei Tuan in the 2023/2024 school year.